2017
DOI: 10.1097/brs.0000000000001704
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Paraspinal Muscle Morphology, Clinical Symptoms, and Functional Status in Patients With Degenerative Cervical Myelopathy

Abstract: 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 35 publications
4
71
1
Order By: Relevance
“…4 ). We base this decision in part on previous work in the cervical spine [ 3 , 5 , 6 , 27 , 41 ]. Such an approach has revealed not only improved inter- and intra-rater reliability when following the spinous process and/or lamina in the cervical spine, but also the ability to discriminate between clinical groups [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 ). We base this decision in part on previous work in the cervical spine [ 3 , 5 , 6 , 27 , 41 ]. Such an approach has revealed not only improved inter- and intra-rater reliability when following the spinous process and/or lamina in the cervical spine, but also the ability to discriminate between clinical groups [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fat (F)-Water (W) Fat Infiltration % MFI = (fat signal)/(fat signal + water signal) *100 Elliott et al, 2014 [ 8 ] From Elliott et al, 2007 [ 47 ] for CSA Intra- rater (0.84–0.99) Inter-rater (0.89–0.96) T1 Axial images aligned parallel to C2–3 IVD; measurements from single slice crossing IVDs C2-C3 and C5-C6 MF SSCerv SSCap SpCap LCap/LCol SCM Manual Quantitative Pixel Intensity Fat Infiltration %MFI = (fat signal)/(fat signal + water signal)*100 CSA Elliott et al, 2015 [ 3 ] Not reported Dixon Measurements from single slice per vertebral level C3-C7; alignment and slice selection not reported MF Manual Fat-Water Fat Infiltration %MFI = (fat signal)/(fat signal + water signal)*100 Abbott et al, 2015 [ 6 ] Intra-rater (0.98) Inter-rater (0.93) Dixon Measurements averaged over 5 slices for each vertebral level C3-C7; Slab alignment not reported. MF + SSCerv (combined) Manual with automatic quartile measure Fat-Water Fat Infiltration %MFI = (fat signal)/(fat signal + water signal)*100 Karlsson et al, 2016 [ 5 ] For muscle fat Intra-rater (0.81–0.93) Inter-rater (0.82–0.97) Dixon Axial images aligned parallel to vertebral segments; measurements averaged over 5 slices for each vertebral level C4-C7 MF Manual Fat-Water Fat Infiltration %MFI = (fat signal)/(fat signal + water signal)*100 CSA Au et al, 2016 [ 57 ] Not reported T1 Axial images aligned parallel to C2–3 intervertebral disc; 3D reconstruction IC, IS, LS, LoCap, LoC, LCap, LCol, MF, LoCap, LoCerv, SSCap, SSCerv, SCM, UT Manual N/A N/A Fortin et al, 2017 [ 27 ] Fortin et al, 2018 [ 81 ] From [ 81 ]:Intra-rater (0.83–0.99) Inter-rater (0.38–0.98) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15] Fortin et al reported that a significant increase in the asymmetry of CSA of multifidus muscles was present at the level below spinal cord compression in the patients with cervical myelopathy. [17]…”
Section: Discussionmentioning
confidence: 99%
“…We expect to achieve an increase in muscle strength that can be quantified by an increase in the functional cross-sectional area of these muscles seen on magnetic resonance images. 38 The study has several weaknesses. First, we discarded 20% to 24% of the data collected because of dislodged or noisy electrodes or implausible values.…”
Section: Discussionmentioning
confidence: 99%